TZDs and Bone: A Review of the Recent Clinical Evidence - Ann V. Schwartz (PPAR Research)
Over the past two years, evidence has emerged that the currently available thiazolidinediones (TZDs), rosiglitazone, and pioglitazone have negative skeletal consequences, at least in women, which are clinically important. Increased fracture risk in women, but not men, was reported for both TZDs, based on analyses of adverse event reports from clinical trials. In short-term clinical trials in women, both TZDs caused more rapid bone loss. In these trials, changes in bone turnover markers suggest a pattern of reduced bone formation without a change in resorption. Although limited, these results support the hypothesis based on rodent and in vitro models that reduced bone formation resulting from activation of peroxisome proliferator-activated receptor-𝛾 (PPAR𝛾) is a central mechanism for TZDs_ effect on bone. Research is needed to better understand the mechanisms of bone loss with TZDs, to identify factors that influence susceptibility to TZD-induced osteoporosis, and to test treatments for its prevention.